REVIEWS (New blackfriars, 1971)
Review in this Article PROCÈS DE L'OBJECTIVITE DE DIEU. LES PRESUPPOSES PHILOSOPHIQUES DE LA CRISE DE L'OBJECTIVITE DE DIEU, by J. Colette, D. Dubarle, A. Dumas, C. Gefiré, J. Granier, M. Kleiber, B. Lemaigre, G. Mainberger, B. Montagnes, B. Quelquejeu. JEAN-PAUL SARTRE: HIS PHILOSOPHY. by René Lafarae. MODERN MISSION DIALOGUE: THEORY AND PRACTICE, edited by Jan Kerkhofs, S.J. Preface by Franz Hengsbach, Bishop of Essen. Introduction by Frank de Graeve, S.J. Commissioned by Pro Mundi Vita, Brussels. THE MECHANISM OF MIND, by Edward de Bono. NEW LIVES, NEW LANDSCAPES, by Nan Fairbrother.